Notting Hill [videorecording (Blu-Ray)] - Curtis, Richard, 1956-; Roberts, Julia, 1967-; Grant, Hugh; Ifans, Rhys, 1967-; McCabe, Richard (Universal Studios Home Entertainment, 2013)
Anna Scott is the world's most famous movie star. Her picture has been plastered on the cover of every magazine and every time she makes a move, the entire world knows about it. William Thacker owns a travel bookstore in the quaint neighborhood of Notting Hill with a roommate from hell and a nonexistent love life. When their paths cross, the couple comes to face with the ultimate question: can two people fall in love with the whole world watching?